2019
DOI: 10.3390/en12071228
|View full text |Cite
|
Sign up to set email alerts
|

Improving Anaerobic Digestion of Sewage Sludge by Hydrogen Addition: Analysis of Microbial Populations and Process Performance

Abstract: The effect of hydrogen pulse addition on digestion performance of sewage sludge was evaluated as a means for studying the increase in efficiency of methane production. Microbial communities were also evaluated to get an insight of the changes caused by the operational modifications of the digester. An energy evaluation of this alternative was performed considering the theoretical process of coupling bioelectrochemical systems (BES) for the treatment of wastewater along with hydrogen production and the subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…In a study of UASB processes operating with molasses wastewater, Eubacteriaceae was found to be one of the dominant phyla in the total bacterial community, and its relative abundance increased from 19.1 ± 6.2% to 30.5 ± 8.7% when OLR was raised from 3.6 to 5.5 COD g/L/d, but started to decrease again with continued increase in OLR [94]. Eubacteriaceae contains many acetogenic members that tolerate rather high content of acetic and propionic acids, and growth of members of this family has also been shown to be favored by H 2 supplementation [68][69][70]95,96]. Thus, one possible hypothesis could be that high OLR gives a high flow of substrate (and H 2 ), which in a certain range is beneficial for members of this family.…”
Section: Correlation Between Bacteria Groups and Olrmentioning
confidence: 99%
“…In a study of UASB processes operating with molasses wastewater, Eubacteriaceae was found to be one of the dominant phyla in the total bacterial community, and its relative abundance increased from 19.1 ± 6.2% to 30.5 ± 8.7% when OLR was raised from 3.6 to 5.5 COD g/L/d, but started to decrease again with continued increase in OLR [94]. Eubacteriaceae contains many acetogenic members that tolerate rather high content of acetic and propionic acids, and growth of members of this family has also been shown to be favored by H 2 supplementation [68][69][70]95,96]. Thus, one possible hypothesis could be that high OLR gives a high flow of substrate (and H 2 ), which in a certain range is beneficial for members of this family.…”
Section: Correlation Between Bacteria Groups and Olrmentioning
confidence: 99%
“…Temperature accelerates the rate of degradation, leading to a shorter time needed to complete the full conversion of the substrate. There are several reports in the literature describing the influence of these parameters when operating under mesophilic and thermophilic regimens [28][29][30] and successfully evaluating different types of wastes, such as swine manure [31,32], sewage sludge [6,33,34], and lipid-rich wastes such as slaughterhouse wastes [35,36]. However, digestion is a complex process and may suffer from instabilities that are mainly associated with accidental overloading in the form of the presence of inhibitors such as sulfur compounds, high ammonia concentration, and volatile fatty acids (VFAs), or inadequate temperature control.…”
Section: Anaerobic Transformation Of Organicsmentioning
confidence: 99%
“…Results regarding this protocol are extremely disperse, obtaining a great diversity of effects in the anaerobic microflora. Martínez et al [33] reported improvements in biogas production with the addition of H 2 gas into a digester treating sewage sludge. Still, the increase in biogas yield was mainly explained by the activity of homoacetogenic microbes, causing the conversion into acetate and subsequently favoring the acetoclastic pathway.…”
Section: Increasing Biomass Activity As a Strategy For Improving Performancementioning
confidence: 99%
“…The evaluation of anaerobic digestion of sewage sludge with different substrates has been widely reported in the literature [ 32 , 33 , 34 ], and it is still under extensive research. There are plenty of reports evaluating the co-digestion of sewage sludge with solid organic wastes, high strength organic streams and different compounds acting as supplements to favor organic degradation [ 35 , 36 , 37 ]. Regarding this last subject is the addition of conductive carbon materials—char, graphene, graphite, activated carbon—to the digestion process that has gained recent interest.…”
Section: Introductionmentioning
confidence: 99%